The role of islamic work ethics on external Libyan Auditors - Nasr, Khayri Abdullah Miftah; Yusoff, Murni; Hassan, Shahir Akram (International Journal of Accounting, Finance and Business, 2024)
This study explores the role of Islamic work ethics on the practices and perspectives of external auditors in Libya, specifically. Utilizing a qualitative research methodology, the study focuses on a population comprising employees auditing offices. A purposive sampling method was employed to select eight external auditors, based on their seniority and expertise in the field. The primary data collection method involved in-depth interviews, with the subsequent data analyzed through qualitative content analysis. Content analysis, as the chosen data analysis method, was conducted on the transcribed interview data. This method was selected due to its robustness in interpreting various forms of content, making it particularly suitable for understanding complex and nuanced perspectives. The study's rationale for employing qualitative content analysis is grounded in its effectiveness in dealing with documents and records, which can serve as the sole source of information or aid in triangulating data for validation purposes. The findings of this study highlight the significant influence of Islamic work ethics on the professional conduct and decision-making processes of Libyan external auditors. The ethical framework provided by Islamic principles not only shapes their auditing practices but also enhances their commitment to integrity, accountability, and transparency. By examining the intersection of cultural, religious, and professional dimensions, this research contributes to a deeper understanding of how Islamic work ethics integrate into and impact the field of auditing in Libya. The study underscores the importance of these ethics in fostering ethical behavior and professionalism, providing valuable insights for policymakers, educators, and practitioners aiming to promote ethical standards in auditing practices.